The battle over marriage : gay rights activism through the media - Moscowitz, Leigh (University of Illinois Press, 2013)
The controversial issue of gay marriage has emerged as a primary battle in the culture wars and a definitive social issue of our time. The subject moved to the forefront of mainstream public debate in 2004, when San Francisco Mayor Gavin Newsom began authorizing same-sex marriage licenses, and it has remained in the center stage through three presidential campaigns and numerous state ballot initiatives. In this thorough analysis, the author examines how prominent news outlets covered this issue from 2003 to 2012, a time when intense news coverage focused unprecedented attention on gay and lesbian life.